2020
DOI: 10.3389/fpsyg.2020.570339
|View full text |Cite
|
Sign up to set email alerts
|

‘Dual Sensory Loss Protocol’ for Communication and Wellbeing of Older Adults With Vision and Hearing Impairment – A Randomized Controlled Trial

Abstract: ObjectivesMany older adults with visual impairment also have significant hearing loss. The aim was to investigate the effectiveness of a newly developed Dual Sensory Loss (DSL) protocol on communication and wellbeing of older persons with DSL and their communication partners (e.g., spouse or child) in the Netherlands and Belgium.MethodsParticipants (N = 131) and their communication partners (n = 113) were randomized in the “DSL-protocol” intervention group or a waiting-list control group. The intervention took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Furthermore, the data suggest that mild bilateral vestibular hypofunction might become clinically relevant as a concomitant factor in cases with multisensory deficits also contributing to and hindering central compensation. This interpretation is supported by analogous data in the elderly for presbyopia and presbyacusis, in which coexistence of sensory deficits led to higher clinical impairment [38,39].…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the data suggest that mild bilateral vestibular hypofunction might become clinically relevant as a concomitant factor in cases with multisensory deficits also contributing to and hindering central compensation. This interpretation is supported by analogous data in the elderly for presbyopia and presbyacusis, in which coexistence of sensory deficits led to higher clinical impairment [38,39].…”
Section: Discussionsupporting
confidence: 63%
“…One possible reason is that SIs influence loneliness by affecting communication with their closest relatives or friends, as loneliness is not caused by being alone but rather by the unmet affective gain of their closest relationship [ 38 ]. Previous studies have indicated that older adults with DSI were more prone to experiencing a breakdown in communication compared with those without SIs [ 39 , 40 ]. Older adults with HI may feel frustrated or embarrassed over their difficulty communicating, resulting in loneliness [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was delivered by occupational therapists (OTs) working in low-vision services and consisted of: (a) optimal use of hearing aids; (b) use of assistive devices and adaptations to the living environment; and (c) coping with DSI and use of effective communication strategies. Although no statistically significant effects of the protocol emerged (effect size standardized mean difference: 0.60), the researchers suggested further studies, adapting the protocol, providing a larger number of OT appointments, and involving social workers or other mental health professionals in the process ( Vreeken et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies focused on seven tools for health care assessments and/or interventions to improve health care for older adults with DSI ( Arauz et al, 1997 ; Bruhn & Dammeyer, 2018 ; Dalby et al, 2009 ; Dupuis et al, 2015 ; Hovaldt et al, 2018 ; Roets-Merken et al, 2014 ; Takano et al, 2016 ; Urqueta Alfaro et al, 2019 ; Vreeken et al, 2020 ). Of all the tools reported, five were standardized clinical assessment instruments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation